Konsekuensi Hukum Terhadap Kreditor Pailit Yang Tidak Mendaftarkan dan Terlambat Mendaftarkan Piutangnya Kepada Kurator Dalam Proses Verifikasi Piutang Kepailitan - Aria Wirajuna; Elisatris Gultom; Sudaryat Sudaryat (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the legal consequences of non-registration or late registration of receivables owned by creditors in the bankruptcy process. Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (PKPU) stipulates that in bankruptcy proceedings, the fulfillment of rights over the bankrupt estate can only be obtained if the creditor registers their receivables for verification. However, there are no specific provisions that explicitly regulate the legal consequences of receivables that are not registered at all or those registered late and thus cannot be verified. This legal uncertainty creates problems in practice, particularly regarding legal protection for creditors and legal certainty in the resolution of bankruptcy cases. Using a normative juridical approach and analyzing relevant legislation and court decisions, this research finds that creditors who fail to register their receivables or register them late lose their rights to receive payments from the bankrupt estate. In other words, receivables that are not verified—either due to non-registration or late registration—are not recognized in the bankruptcy process. This conclusion highlights the importance of creditors understanding the procedures for registering receivables in bankruptcy in order to protect their rights. The study also recommends that existing legal regulations provide clearer guidance regarding the consequences of delayed or unregistered receivables to ensure legal certainty and fair protection for all parties involved in bankruptcy proceedings.